إدارة المعرفة "أسوب متكامل للإدارة الحديثة - واضح فواز, واضح فواز (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(--scale-factor)*94.70px); top: calc(var(--scale-factor)*345.65px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898145);" role="presentation">This study deals with a modern methods of management, depending on the various research to study the <span dir="ltr" style="left: calc(var(--scale-factor)*82.22px); top: calc(var(--scale-factor)*357.05px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921208);" role="presentation">importance of knowledge for the success or failure of any institution , as the availability of knowledge and <span dir="ltr" style="left: calc(var(--scale-factor)*82.22px); top: calc(var(--scale-factor)*368.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894956);" role="presentation">to understand and use in a timely manne<span dir="ltr" style="left: calc(var(--scale-factor)*243.53px); top: calc(var(--scale-factor)*368.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920591);" role="presentation">r may contribute to the transformation of the organization from a <span dir="ltr" style="left: calc(var(--scale-factor)*82.22px); top: calc(var(--scale-factor)*380.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914446);" role="presentation">certain competitive position to the competitive position better , and this premise came the attention of <span dir="ltr" style="left: calc(var(--scale-factor)*82.22px); top: calc(var(--scale-factor)*391.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90315);" role="presentation">researchers and thinkers in the field of management in order to determine an integrat<span dir="ltr" style="left: calc(var(--scale-factor)*420.82px); top: calc(var(--scale-factor)*391.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887114);" role="presentation">ed management model <span dir="ltr" style="left: calc(var(--scale-factor)*82.22px); top: calc(var(--scale-factor)*403.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902444);" role="presentation">based on knowledge as the most important element of the production elements in the modern econom